The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1113/expphysiol.2006.034934
|View full text |Cite
|
Sign up to set email alerts
|

The effects of face cooling during hyperthermic exercise in man: evidence for an integrated thermal, neuroendocrine and behavioural response

Abstract: The present study investigated whether face cooling reduced both the perceived exertion (RPE) and prolactin (PRL) release during hyperthermic exercise. Ten, non-heat-acclimated males (23 ± 2 years; maximal oxygen consumption, 56 ± 7 ml kg -1 min -1 [mean ± S.D.]) exercised for 40 min on a cycle ergometer at 65% of their peak aerobic power, at an ambient temperature of 33• C (27% relative humidity) with (FC) and without face cooling as a control (CON). With FC, forehead temperature was maintained ∼6• C lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
3
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 37 publications
(71 reference statements)
1
55
3
1
Order By: Relevance
“…Other studies have investigated the role of sensory mechanisms in the face. Mundel et al (2007) investigated spraying cold water (~4 °C) on the face during exercise at 65% VO 2peak for 40 min in the heat (33 °C, 27% humidity). Heart rate was five beats/min lower with facial cooling, and both rating of perceived exertion (RPE) and thermal comfort were also lower.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the role of sensory mechanisms in the face. Mundel et al (2007) investigated spraying cold water (~4 °C) on the face during exercise at 65% VO 2peak for 40 min in the heat (33 °C, 27% humidity). Heart rate was five beats/min lower with facial cooling, and both rating of perceived exertion (RPE) and thermal comfort were also lower.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, they induced passive heat stress with water immersion, in which the head and face are not heated directly. 6,10 Whole-body heat stress that includes the head and face (ie, heat stress chamber) might effectively modulate cardiovascular, hormonal, and protective chaperones (extracellular HSP72). For example, cardiovascular work increases to stabilize blood pressure during heat-induced skin vasodilation.…”
mentioning
confidence: 99%
“…Hayashi and Tokura 48 found that body temperature during exercise was attenuated during approximately 60 minutes of cycling in a hot environment when head cooling was worn. In contrast, Mündel et al 49 and Ansley et al 50 discovered that body temperature postexercise was unchanged when head cooling was used compared with no cooling. The effect of head cooling on exercise performance is limited, although evidence does support its use in increasing time to fatigue.…”
Section: Head Coolingmentioning
confidence: 97%